Public Sector Governance and the Medium-Term National Action Agenda for Productivity (MNAAP) - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2000)
This short note provides a framework for looking at public sector governance and productivity improvements. It argues that the role of government in enhancing productivity growth is two-fold. First, government should provide an environment that is conducive in improving total factor productivity in private sector production. Second, government should work to increase the productivity of the public sector itself. In terms of providing the appropriate economic setting that is favorable to private-sector-led development, government needs (1) to provide the macroeconomic and the microeconomic environment that will establish incentives for firms/individuals to act in accordance with the invisible hand had there been no market imperfection, (2) to provide the institutional infrastructure (i.e., property rights, law and order, rules and even application and enforcement of the same) that markets need to work efficiently; and (3) to ensure the financing/provision of adequate basic health care and education, and basic physical infrastructure (World Bank 1992). In particular, the instruments that government may use in this regard are include (1) direct government interventions in the product markets as defined by the regulatory structure in strategic sectors, and (2) economy-wide policies like financial liberalization, trade liberalization, and foreign investments liberalization. On the other hand, (1) budget reform (2) the installation of a system of performance measurement and incentive in the public sector, (3) the re-engineering of the bureaucracy, (4) the combating of corruption, and (5) decentralization are the key features of a program that will increase the productivity of government operations.
Keywords: 330; productivity; Produktivität; Wirtschaftsreform; Verwaltungsreform; Leistungsanreiz; Öffentlicher Sektor; Philippinen